2008
DOI: 10.1016/j.neuroimage.2007.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cortical thickness correlates of cognitive performance: Reliability across MRI scan sessions, scanners, and field strengths

Abstract: In normal humans, relationships between cognitive test performance and cortical structure have received little study, in part, because of the paucity of tools for measuring cortical structure. Computational morphometric methods have recently been developed that enable the measurement of cortical thickness from MRI data, but little data exist on their reliability. We undertook this study to evaluate the reliability of an automated cortical thickness measurement method to detect correlates of interest between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
223
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(239 citation statements)
references
References 61 publications
14
223
1
1
Order By: Relevance
“…Of note, T1w scans flagged by a combination of FD¯ and QC ratings: (1) increased with increasing age, and (2) exhibited considerably reduced global and regional estimates of gray matter volume and thickness. Reductions in gray matter volume and thickness are well documented as a hallmark of healthy aging and cognitive decline [DeKosky and Scheff, 1990; Dickerson et al, 2008, 2012; Sowell et al, 2003]. We suggest that these effects may in some cases be overestimated, particularly in certain brain locations, by the inclusion of biased estimates from T1w structural scans with motion artifacts.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Of note, T1w scans flagged by a combination of FD¯ and QC ratings: (1) increased with increasing age, and (2) exhibited considerably reduced global and regional estimates of gray matter volume and thickness. Reductions in gray matter volume and thickness are well documented as a hallmark of healthy aging and cognitive decline [DeKosky and Scheff, 1990; Dickerson et al, 2008, 2012; Sowell et al, 2003]. We suggest that these effects may in some cases be overestimated, particularly in certain brain locations, by the inclusion of biased estimates from T1w structural scans with motion artifacts.…”
Section: Discussionmentioning
confidence: 79%
“…FS processing has been demonstrated to have high test–retest reliability in identifying and measuring various aspects of brain anatomy across scanner manufacturers and field strengths [Dickerson et al, 2008; Han et al, 2006; Jovicich et al, 2006; Morey et al, 2010; Reuter et al, 2012]. However, it is important to point out that the FS processing pipeline requires careful inspection of processed outputs to ensure that segmentations and reconstructions are spatially accurate and anatomically correct.…”
Section: Methodsmentioning
confidence: 99%
“…We coined the term "SuperAger" for these individuals with the assumption that they had a high likelihood of having avoided the involutional effects of age on memory function. Previous investigations of this cohort (Harrison et al, 2012) found that in a small group of SuperAgers (N ϭ 12), there was little evidence of the age-related cortical atrophy that has been demonstrated in numerous studies on cognitively average populations of healthy elderly (Salat et al, 2004;Yao et al, 2012). Most surprisingly, a patch of anterior cingulate cortex was thicker in the SuperAger group than even in cognitively normal 50-to 65-year-old subjects (Harrison et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
“…Previous efforts demonstrated high scan–rescan reproducibility of the neuroimaging included of the volumetric measurements for subcortical brain structures (Maclaren et al., 2014), cortical gray matter thickness (Dickerson et al., 2008; Han et al., 2006; Li et al., 2015), and diffusion tensor measurements (Acheson et al., 2017; Jovicich et al., 2014). Likewise, several prior studies quantified scan–rescan stability and reproducibility of the MRS measurements at 3T (Wellard, Briellmann, Jennings, & Jackson, 2005; Wijtenburg & Knight‐Scott, 2011; Wijtenburg et al., 2013).…”
Section: Discussionmentioning
confidence: 99%